Exaiptasia pallida - Grajales, Alejandro; Rodríguez, Estefanía (Zenodo, 2014)
Exaiptasia pallida (Agassiz in Verrill, 1864) comb. nov. (Figs. 8–10, Table 3) Actinia diaphana Rapp, 1829 Cribina diaphana : Deshayes & Milne Edwards 1840 Actinia elongata Delle Chiaje, 1841 Adamsia diaphana: Milne Edwards 1857 Dysactis pallida Agassiz in Verrill, 1864 Bartholomea tagetes [ sic ] Duchassaing de Fombressin & Michelotti, 1864 Bartholomea inula [ sic ] Duchassaing de Fombressin & Michelotti, 1864 Dysactis mimosa Duchassaing de Fombressin & Michelotti, 1864 Bartholomea inula: Duchassaing de Fombressin & Michelotti, 1866 Dysactis minuta Verrill, 1867 (1866) Paranthea minuta: Verrill 1868 Paranthea pallida: Verrill 1868 Disactis mimosa [ sic ]: Duchassaing 1870 Aiptasia saxicola Andres, 1881 Aiptasia diaphana : Andres 1883 (1884) Aiptasia [ sic ] Agassizii: Andres 1883 (1884) Aiptasia inula: Andres 1883 (1884) Aiptasia minuta: Andres 1883 (1884) Aiptasia mimosa: Andres 1883 (1884) Aiptasia tagetes: Andres 1883 (1884) Aiptasia pallida : McMurrich 1887 Aiptasia leiodactyla Pax, 1910 Aiptasia insignis Carlgren, 1941 Aiptasioides pallida: Stephenson 1918 Aiptasiomorpha diaphana : Stephenson 1920 Aiptasiomorpha leiodactyla: Stephenson 1920 Bartholomea tagetes: Stephenson 1920 Aiptasia pulchella Carlgren, 1943 Aiptasia californica Carlgren, 1952 Aiptasia tagetes : Atoda 1954 Aiptasiomorpha minuta: Uchida & Soyama 2001 Aipstasia [ sic ] pulchella: Reimer et al. 2007 Material examined. (See Appendix 1). Comparative material examined. Aiptasia insignis Carlgren, 1941; SMNH-type 4510 (three syntypes). South Atlantic Ocean, Saint Helena, off Jamestown. Leg. Th. Mortenseni 0 1 Feb 1930. Aiptasia parva Carlgren, 1938; SMNH-type 4053 (six syntypes, only two loaned). South Atlantic Ocean, South Africa, East London. Leg. Swedish South African Expedition 1935. Aiptasia parva Carlgren, 1938; SMNH-type 4054 (three syntypes). South Atlantic Ocean, South Africa, East London. Leg. Swedish South African Expedition 1935. Dysactis pallida Agassiz in Verrill, 1864; MCZ SCOR-1004 (two syntypes). North ...